2019
DOI: 10.1097/cmr.0000000000000504
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of treatment and BRAF testing with immune checkpoint inhibitors and targeted therapy in patients with metastatic melanoma presumed to be BRAF positive

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 44 publications
4
7
2
Order By: Relevance
“…Similar treatment patterns were also observed in a recent analysis of two US claims databases that evaluated patients with BRAF Mut tumors with claims filed between 1 January 2014 and 30 June 2016 (Truven Health Analytics MarketScan, part of the IBM Watson Health™ business, MI, USA), or 30 September 2016 (IQVIA, NC, USA) [19].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Similar treatment patterns were also observed in a recent analysis of two US claims databases that evaluated patients with BRAF Mut tumors with claims filed between 1 January 2014 and 30 June 2016 (Truven Health Analytics MarketScan, part of the IBM Watson Health™ business, MI, USA), or 30 September 2016 (IQVIA, NC, USA) [19].…”
Section: Discussionsupporting
confidence: 68%
“…The use of other targeted therapies (i.e., rituximab, bevacizumab, bortezomib and ruxolitinib phosphate) was sparse and occurred mostly as single-agent use in the first- and second-line settings for patients with stage IV melanoma or those who did not meet the criteria for receiving one of the other therapeutic options. Although it has also been suggested that targeted therapy with BRAF/MEK inhibitors may be used for patients with BRAF Mut tumors who have a higher comorbidity burden, including brain metastases [19], recent analyses suggest that checkpoint inhibitors may be the preferred first-line option for patients with brain metastases, given that they appear to result in comparable overall response rates but higher rates of durable intracranial responses [26]. In stage III melanoma, checkpoint inhibitors were used more commonly in BRAF Mut compared with BRAF Wt melanomas, although the reasons for this could not be determined by this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, three previous observational studies have evaluated IO/TT treatment patterns in patients with BRAF+ advanced melanoma [4,6,8]. In contrast to our study, Luke et al [6] observed that most patients in the realworld setting were treated in 1L with TT (64%), as compared to IO (36%).…”
Section: Relation To Prior Workcontrasting
confidence: 79%
“…To date, three previous observational studies have evaluated IO/TT treatment patterns in patients with BRAF+ advanced melanoma [4,6,8]. In contrast to our study, Luke et al .…”
Section: Discussioncontrasting
confidence: 61%